Men's sheds as an alternative healthcare route? A qualitative study of the impact of Men's sheds on user's health improvement behaviours - Danielle Kelly; Artur Steiner; Helen Mason; Simon Teasdale (BMC, 2021)
Abstract Background Men's health is a globally underrepresented area of research and policy. With men facing numerous healthcare barriers, there are calls for more 'male friendly' approaches to health improvement that take into consideration differing male behaviours and attitudes towards health. Men's Sheds are community-based organisations delivering practical and social activities that encourage positive health behaviours. While Sheds have been recognised for their health and wellbeing benefits to men, research has yet to explore the impacts of Sheds on male health improvement and their potential role as a preventative gendered public health measure. Methods The study used in-depth interviews with 62 Shed members from five Sheds to investigate the impacts of Shed activity on the health improvement behaviours and attitudes of Shed users. Findings from the qualitative study were used to propose a set of pathways in which Sheds activity led to positive health engagement. Results The proposed pathways suggest that there are many different and interlinked ways in which Shed activities can impact on the health behaviours and attitudes of Shed users. Through participation in various practical and social activities in an inclusive environment, Shed users reported increases in their health seeking behaviours, improved perspectives on and management of their personal health, and an increased ability to overcome illness and recover. Conclusions Where male friendly health provision has been lacking, this study suggests how Men's Shed activities can provide positive male health outcomes, often in unexpected and non-obvious ways. In particular, the proposed visual pathways are important to inform policymakers and practitioners of the ways in that Sheds may contribute to engaging men in health improvement practices and increase their health knowledge. This study also provides a structure from which further studies can measure and evaluate Shed health impacts.